Intrathecal IgM production at clinical onset correlates with a more severe disease course in multiple sclerosis. Issue 8 (30th March 2006) - Perini, P; Ranzato, F; Calabrese, M; Battistin, L; Gallo, P
Abstract : The intrathecal synthesis of IgM, determined at clinical onset in patients with multiple sclerosis, was found to correlate with the degree of disability (as evaluated by means of the Expanded Disability Status Scale) reached 15 years later (p<0.001). Moreover, a significant inverse correlation was observed between the value of the IgM index and time to the first relapse (p<0.001) and the initiation of the progressive phase of the disease (p = 0.01). The prognostic value of IgM in the CSF is confirmed in previous reports as well as by our study. If these findings are confirmed in patients with multiple sclerosis in a larger series, a helpful biological marker for selecting patients for immunomodulatory treatments will be available to neurologists.